Posições maternas e sua influência no desfecho do parto e nascimento: um estudo caso-controle - Farias, Laryssa Miranda Vidal Cavalcante (2020)
The aim of the study was to assess maternal positions and their influence on the outcomes of childbirth and birth. This is an observational, correlational, case-control study carried out between the months of February 2019 and April 2020 at a reference maternity hospital in Fortaleza-Ceará. The population was composed of all nulliparous women who had a vaginal delivery at the institution during the research and who met the inclusion and exclusion criteria defined for the study. There were 138 women in the control group (nulliparous women in labor and giving birth in non-vertical positions) and 60 women in the case group (nulliparous women in labor and giving birth in vertical positions). Data were collected using a closed questions form, compiled and analyzed in SPSS. Fisher's Statistical Test was used and OddsRation and Confidence Interval were applied when significant. The project was submitted to the research ethics committee and approved - No. 3,545,134. There was an association between age group and occurrence of upright delivery (p = 0.011), with it being observed that women over the age of 34 have 12.59 more chances (OR = 12.59; CI = 1.44- 110,30) of giving birth in vertical positions. Regarding the conditions of the perineum, there was no association between the variables position of delivery and presence of perineal lacerations. It was found association between deliveries assisted by nurses and upright delivery (p <0.001) with an increase of a 4.53 in the chances of upright delivery when performed by these professionals. It was possible to detect significant differences when there was medical advice involved (p = 0.045), observing an increase of 86% in the chance of carrying out the upright delivery when the advice was from other professionals that not the doctor. As for neonatal vitality, almost all newborns had an Apgar score ≥ 7 in the first and fifth minutes of life, indicating good vitality. There was a statistical relation between the position of giving birth and woman's satisfaction (p = 0.021). For women who performed a vertical birth, there is a 6.63 times greater chance of being very satisfied with the delivery, when compared to those who are dissatisfied or not very satisfied. It is concluded that there is a lower prevalence of not recommended practices in verticalized positions, professional nurses stand out in encouraging these positions and there is a greater maternal satisfaction in women who have given birth in verticalized positions. Regarding neonatal outcomes, both positions were satisfactory for neonates.